Pengaruh Kualitas Produk dan Kualitas Pelayanan terhadap Minat Beli Konsumen pada UD. Ramli Aek Tolang Kabupaten Tapanuli Tengah - Rahmad Wirawan Nasution; Rosmita Ambarita; Tiurlina Hasmawati Sihite (EBISMA : Jurnal Ekonomi, Bisnis, Manajemen dan Akuntansi, 2026)
This study aims to analyze the effect of product quality and service quality on consumer purchase intention at UD. Ramli Aek Tolang, Central Tapanuli Regency. The research method used is a quantitative approach with a correlational design. The population consisted of 450 consumers, with a sample of 45 respondents determined using a percentage sampling technique. Data were collected through questionnaires, observations, and interviews. Data analysis was conducted using multiple linear regression with the assistance of SPSS software. The results indicate that partially, both product quality and service quality have a positive and significant effect on consumer purchase intention. Simultaneously, both variables also have a significant effect, with a coefficient of determination of 0.750, indicating that 75% of the variation in purchase intention can be explained by product and service quality. Product quality has a more dominant influence compared to service quality. Therefore, improving both product and service quality simultaneously can be an effective strategy to enhance consumer purchase intention.